Modified hexagonal boron nitride, preparation method and application thereof, self-lubricating phenolic laminated composite material and preparation method thereof

By using modified hexagonal boron nitride in phenolic laminated composite materials, the transfer film formation and silica composite characteristics of its water-lubricated conditions are solved, and the wear problem of traditional materials under water-lubricated conditions is achieved, achieving high wear resistance and low friction effects.

CN119875392AActive Publication Date: 2025-04-25QINGDAO RESOURCE CHEM & NEW MATERIALS RES CENT +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510069002.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-25
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

Traditional phenolic laminated composite materials lack good self-lubricating properties, resulting in easy wear and scratching under water lubrication conditions, making it difficult to form an excellent boundary lubricating film, affecting the normal operation and life of the bearing.

Method used

By introducing modified hexagonal boron nitride as a lubricating material, the modified hexagonal boron nitride includes hexagonal boron nitride and silicon dioxide bonded with it, and a boric acid hydrated layer and hard-loaded silicon dioxide are formed by hydrolysis reaction to form an in-situ composite of the boric acid hydrated layer and the hard-loaded silicon dioxide to enhance the binding force and shear resistance of the transfer film.

Benefits of technology

The wear resistance of the phenolic laminated composite material is significantly improved, the service life of the material is extended, and excellent friction lubrication performance is achieved under water lubricating conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875392A_ABST
    Figure CN119875392A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of self-lubricating materials, and particularly relates to modified hexagonal boron nitride, a preparation method and application of the modified hexagonal boron nitride, a self-lubricating phenolic laminated composite material and a preparation method of the self-lubricating phenolic laminated composite material. The modified hexagonal boron nitride provided by the invention comprises hexagonal boron nitride and silicon dioxide bonded with the hexagonal boron nitride through a silicon-oxygen bond. In the water lubrication process, hexagonal boron nitride and silicon dioxide particles are easily released to a friction interface; the hexagonal boron nitride nano material can form an excellent transfer film on a friction interface under a water lubrication condition, and can be subjected to hydrolysis reaction with water to form a boric acid hydration layer to achieve an excellent lubrication effect, so that the wear rate of the material can be greatly reduced; the in-situ loaded silicon dioxide particles can participate in the forming process of the hexagonal boron nitride transfer membrane under the action of friction shearing, the binding force of the transfer membrane and a friction pair is enhanced, the elastic modulus, the anti-shearing performance and the bearing capacity of the transfer membrane are improved, and excellent wear resistance is shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of self-lubricating materials, and specifically relates to a modified hexagonal boron nitride and a preparation method and application thereof, a self-lubricating phenolic laminate composite material and a preparation method thereof. Background Art

[0002] Traditional phenolic laminated composite materials use thermosetting liquid phenolic resin or modified phenolic resin as resin binder and cotton fiber fabric as load-bearing reinforcement unit. After being stacked layer by layer and heated and pressed, they are made into various specifications of plates, pipes, rods, etc. They have high mechanical properties, heat resistance, dielectric properties, water resistance, moisture resistance, oil resistance, etc. Due to its excellent performance, it plays an important role in the field of mechanical engineering, especially in the field of water-lubricated bearings for shipping ship tail shafts, and has played a vital role for a long time in the past, such as the famous British Feilong TENMAT series bearings.

[0003] However, traditional phenolic laminated composite materials lack good self-lubricating properties. In order to improve their self-lubricating properties, the industry has added a lubricating phase to the composite materials. The current lubricating phase is mainly graphite or molybdenum disulfide. However, due to the addition of the lubricating phase, the phenolic laminated material has high hardness and high brittleness. Under water lubrication conditions, it is easy to cause serious wear and scratches on the bearing surface during the running-in process due to the transfer of the lubricating phase material. It is difficult to promote the formation of an excellent boundary lubrication film, which affects the lubrication and wear of the bearing, and further affects the normal operation and life of the bearing. Summary of the invention

[0004] In view of this, the present invention provides a modified hexagonal boron nitride and a preparation method and application thereof, a self-lubricating phenolic laminated composite material and a preparation method thereof. The self-lubricating phenolic laminated composite material prepared by using the modified hexagonal boron nitride provided by the present invention as a lubricating material can significantly improve its wear resistance.

[0005] In order to solve the above technical problems, the present invention provides a modified hexagonal boron nitride, comprising hexagonal boron nitride and silicon dioxide bonded to the hexagonal boron nitride by a silicon-oxygen bond.

[0006] Preferably, the mass ratio of silicon dioxide to hexagonal boron nitride in the modified hexagonal boron nitride is 5 to 30:100.

[0007] Preferably, the method comprises the following steps:

[0008] The hexagonal boron nitride and the strong base solution are first mixed to perform surface hydrolysis activation to obtain hydroxylated hexagonal boron nitride;

[0009] The hydroxylated hexagonal boron nitride, tetraethoxysilane, surfactant, alkaline solution and solvent are mixed for a second time and subjected to a hydrolysis reaction to obtain the modified hexagonal boron nitride.

[0010] Preferably, the strong alkali solution includes one or more of a sodium hydroxide solution, a potassium hydroxide solution and a lithium hydroxide solution; the molar concentration of the strong alkali solution is 3 to 6 mol / L;

[0011] The particle size of the hexagonal boron nitride is 5 to 10 μm; the volume ratio of the mass of the hexagonal boron nitride to the strong alkaline solution is 1 g: 10 to 30 mL;

[0012] The temperature of the surface hydrolysis activation is 90 to 120° C.; the time of the surface hydrolysis activation is 10 to 36 hours.

[0013] Preferably, the alkaline solution includes one or more of a mixed solution of NH3 and NH4Cl, a mixed solution of NH3 and NH4HCO3, and NH3·H2O; the pH value of the alkaline solution is 8 to 10;

[0014] The surfactant includes one or more of dodecyltrimethylammonium chloride, N-dodecyldimethylamine, fatty acid soap, sodium cis-9-octadecenoate and sodium laurate soap;

[0015] The solvent includes an organic solvent and water, wherein the organic solvent includes one or more of ethanol, ethylene glycol, glycerol, tetrahydrofuran, toluene, chlorobenzene and dichlorobenzene; the volume ratio of the organic solvent to water is 1:4-6;

[0016] The mass ratio of the surface hydroxylated hexagonal boron nitride to the volume ratio of the solvent is 1 g: 10 to 50 mL;

[0017] The volume ratio of tetraethoxysilane to solvent is 1:4-30;

[0018] The mass ratio of the surfactant to the solvent is 1:20 to 100;

[0019] The mass ratio of the alkaline solution to the volume of the solvent is 1 g: 20-35 mL;

[0020] The temperature of the hydrolysis reaction is 15-35° C. and the time is 12-36 hours.

[0021] The present invention also provides the use of the modified hexagonal boron nitride described in the above technical solution or the modified hexagonal boron nitride prepared by the preparation method described in the above technical solution as a lubricant.

[0022] The present invention also provides a self-lubricating phenolic laminate composite material, comprising the following components in percentage by mass:

[0023] Phenolic resin 40-55%;

[0024] Textile fiber cloth 35-57%;

[0025] Lubricant 3-15%;

[0026] The lubricant is the modified hexagonal boron nitride described in the above technical solution or the modified hexagonal boron nitride prepared by the preparation method described in the above technical solution.

[0027] Preferably, the fibers in the textile fiber cloth include one or more of polyester fibers, cotton fibers, acrylic fibers, polytetrafluoroethylene fibers and aramid fibers.

[0028] The present invention also provides a method for preparing the self-lubricating phenolic laminate composite material described in the above technical solution, comprising the following steps:

[0029] Mixing the lubricant, phenolic resin and diluent to obtain a phenolic resin mixed solution;

[0030] impregnating the textile fiber cloth with the phenolic resin mixed solution and then drying to obtain a pre-impregnated textile fiber cloth;

[0031] The pre-impregnated textile fiber cloth is formed and then sintered and cured to obtain the self-lubricating phenolic laminate composite material.

[0032] Preferably, the amount of glue applied after the textile fiber cloth is impregnated with the phenolic resin mixed solution is 45 to 65%;

[0033] The drying temperature is 100-120°C and the drying time is 1-10 minutes;

[0034] The sintering and curing comprises sequentially performing a first sintering and curing, a second sintering and curing, and a third sintering and curing;

[0035] The temperature of the first sintering and curing is 75-85° C., and the holding time of the first sintering and curing is 90-120 min;

[0036] The temperature of the second sintering and curing is 100-120° C., and the insulation time of the second sintering and curing is 90-120 min;

[0037] The temperature of the third sintering and curing is 140-160° C., and the heat preservation time of the third sintering and curing is 120-240 minutes.

[0038] The present invention provides a modified hexagonal boron nitride, comprising hexagonal boron nitride and silicon dioxide bonded to the hexagonal boron nitride by a silicon-oxygen bond. The present invention introduces high-hardness silicon dioxide into the surface of the hexagonal boron nitride material, which can strengthen the synergistic effect between silicon dioxide and hexagonal boron nitride; in the process of water lubrication, hexagonal boron nitride and silicon dioxide particles are easily released to the friction interface; on the one hand, under water lubrication conditions, the hexagonal boron nitride nanomaterial can form an excellent transfer film at the friction interface, and can react with water to form a boric acid hydration layer to play an excellent lubricating role, which can greatly reduce the material wear rate; on the other hand, the in-situ loaded silicon dioxide particles can participate in the formation process of the hexagonal boron nitride transfer film under the action of friction shear, enhance the bonding force between the transfer film and the friction pair, improve the elastic modulus, shear resistance and load-bearing capacity of the transfer film, and show excellent wear resistance. The self-lubricating phenolic laminated composite material prepared by using the modified hexagonal boron nitride provided by the present invention as a lubricating material can significantly improve its wear resistance and extend the service life of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is the SEM image of the modified hexagonal boron nitride prepared in Example 1. DETAILED DESCRIPTION

[0040] The invention provides a modified hexagonal boron nitride, comprising hexagonal boron nitride and silicon dioxide bonded to the hexagonal boron nitride by silicon-oxygen bonds.

[0041] As a specific embodiment of the present invention, the mass ratio of silicon dioxide to hexagonal boron nitride in the modified hexagonal boron nitride can be 5 to 30:100, or 8 to 20:100; the silicon dioxide is loaded on the surface of the hexagonal boron nitride; the average particle size of the silicon dioxide can be 10 to 30 nm, or 10 to 20 nm; the average particle size of the hexagonal boron nitride can be 5 to 10 μm, or 5 to 10 μm.

[0042] In the present invention, hexagonal boron nitride has the properties of non-toxicity, high temperature resistance, corrosion resistance, high thermal conductivity, high insulation, and high lubricity. It is easily transferred to the surface of the friction pair bearing under water lubrication conditions, and under the action of friction shear, the hexagonal boron nitride nanomaterial undergoes a hydrolysis reaction with water at the friction interface to form a boric acid hydration layer, which plays an excellent lubricating role and can greatly reduce the material wear rate. The present invention introduces silicon dioxide into boron nitride to obtain modified hexagonal boron nitride. The modified hexagonal boron nitride provided by the present invention is used to prepare a phenolic laminate composite material, which can more effectively improve the formation of a self-lubricating transfer film on the friction pair surface under water lubrication conditions, and greatly improve the friction and wear performance under water lubrication conditions.

[0043] The present invention also provides a method for preparing the modified hexagonal boron nitride described in the above technical solution, comprising the following steps:

[0044] The hexagonal boron nitride and the strong base solution are first mixed to perform surface hydrolysis activation to obtain hydroxylated hexagonal boron nitride;

[0045] The hydroxylated hexagonal boron nitride, tetraethoxysilane, surfactant, alkaline solution and solvent are mixed for a second time and subjected to a hydrolysis reaction to obtain the modified hexagonal boron nitride.

[0046] The present invention first mixes hexagonal boron nitride and a strong alkali solution for surface hydrolysis activation to obtain hydroxylated hexagonal boron nitride. As a specific embodiment of the present invention, the particle size of the hexagonal boron nitride can be 5 to 10 μm, specifically 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm. As a specific embodiment of the present invention, the strong alkali solution can include one or more of sodium hydroxide solution, potassium hydroxide solution and lithium hydroxide solution, specifically sodium hydroxide solution, potassium hydroxide solution or lithium hydroxide solution; the molar concentration of the strong alkali solution can be 3 to 6 mol / L, specifically 3 mol / L, 4 mol / L, 5 mol / L or 6 mol / L. As a specific embodiment of the present invention, the mass ratio of the hexagonal boron nitride to the strong alkali solution can be 1 g: 10 to 30 mL, specifically 1 g: 10 mL, 1 g: 15 mL, 1 g: 20 mL, 1 g: 25 mL or 1 g: 30 mL. As a specific embodiment of the present invention, the first mixing can be performed under ultrasonic conditions, and the ultrasonic time can be 10 to 30 minutes, or 15 to 25 minutes. The present invention has no special limitation on the frequency of the ultrasonic, as long as it can mix evenly.

[0047] As a specific embodiment of the present invention, the temperature of the surface hydrolysis activation can be 90-120°C, specifically 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C; the time of the surface hydrolysis activation can be 10-36h, specifically 10h, 15h, 20h, 25h, 30h, 35h or 36h. As a specific embodiment of the present invention, the surface hydrolysis activation can be accompanied by stirring, and the present invention has no special limitation on the stirring, as long as it can fully react.

[0048] The invention uses a strong base to modify hexagonal boron nitride to obtain hydroxylated boron nitride; the compatibility between the surface of boron nitride and resin is improved, which is conducive to uniform dispersion; and active reaction sites are provided for subsequent treatment (hydrolysis reaction), which facilitates the in-situ growth of silicon dioxide on the surface of hexagonal boron nitride. On the other hand, hydroxyl groups in the modified hexagonal boron nitride (hydroxyl groups from the surface of the incompletely reacted hydroxylated boron nitride or the surface of silicon dioxide particles) can undergo further chemical crosslinking reaction with phenolic resin and textile fiber cloth, thereby improving the bonding strength between the hexagonal boron nitride nanomaterial and the phenolic resin and textile fiber cloth, and further improving the mechanical properties of the material such as wear resistance and compression strength.

[0049] As a specific embodiment of the present invention, after the surface hydrolysis activation, the process may further include: separating the solid-liquid separation of the system after the surface hydrolysis activation, washing and drying the solid obtained by the solid-liquid separation in sequence, and obtaining hydroxylated hexagonal boron nitride. As a specific embodiment of the present invention, the solid-liquid separation may be filtration; the washing detergent may be water, and the water may be deionized water; the drying temperature may be 70 to 90°C, and may also be 75 to 80°C. The present invention has no special requirements for the drying time, as long as the solvent on the solid surface can be removed.

[0050] After obtaining the hydroxylated hexagonal boron nitride, the present invention secondly mixes the hydroxylated hexagonal boron nitride, tetraethoxysilane, a surfactant, an alkaline solution and a solvent, and performs a hydrolysis reaction to obtain the modified hexagonal boron nitride. As a specific embodiment of the present invention, the second mixing may include the following steps:

[0051] dissolving tetraethoxysilane in a portion of the solvent to obtain a tetraethoxysilane solution;

[0052] dispersing the hydroxylated hexagonal boron nitride in the remaining solvent to obtain a hydroxylated hexagonal boron nitride dispersion;

[0053] Adding an alkaline solution and a surfactant to the hydroxylated hexagonal boron nitride dispersion in sequence to obtain a mixed solution;

[0054] The tetraethoxysilane solution was added dropwise to the mixed solution.

[0055] The present invention dissolves tetraethoxysilane in a part of the solvent to obtain a tetraethoxysilane solution. The present invention has no special limitation on the mass concentration of the tetraethoxysilane solution. The present invention has no special limitation on the dissolution, as long as it can be completely dissolved. As a specific embodiment of the present invention, the solvent includes an organic solvent and water; the organic solvent may include one or more of ethanol, ethylene glycol, glycerol, tetrahydrofuran, toluene, chlorobenzene and dichlorobenzene, and may specifically be ethanol, ethylene glycol, glycerol, tetrahydrofuran, toluene, chlorobenzene or dichlorobenzene; the volume ratio of the organic solvent to water may be 1:4 to 6, and may specifically be 1:4, 1:5 or 1:6.

[0056] The present invention disperses hydroxylated hexagonal boron nitride in the remaining solvent to obtain a hydroxylated hexagonal boron nitride dispersion. As a specific embodiment of the present invention, the dispersion can be carried out under ultrasonic conditions, and the ultrasonic time can be 10 to 20 minutes, or 15 to 18 minutes. The present invention has no special limitation on the power of the ultrasound as long as it can be evenly dispersed.

[0057] After obtaining the hydroxylated hexagonal boron nitride dispersion, the present invention sequentially adds an alkaline solution and a surfactant to the hydroxylated hexagonal boron nitride dispersion to obtain a mixed solution. As a specific embodiment of the present invention, the alkaline solution may include one or more of a mixed solution of NH3 and NH4Cl, a mixed solution of NH3 and NH4HCO3, and NH3·H2O, and may specifically be a mixed solution of NH3 and NH4Cl, a mixed solution of NH3 and NH4HCO3, or NH3·H2O; the pH value of the alkaline solution may be 8 to 10, and may specifically be 8, 9, or 10. As a specific embodiment of the present invention, the surfactant includes one or more of dodecyltrimethylammonium chloride, N-dodecyldimethylamine, fatty acid soap, sodium cis-9-octadecenoate, and sodium laurate soap, and may specifically be dodecyltrimethylammonium chloride, N-dodecyldimethylamine, fatty acid soap, sodium cis-9-octadecenoate, or sodium laurate soap. In the present invention, the surfactant can improve the dispersibility and stability of tetraethoxysilane and surface hydroxylated hexagonal boron nitride in the solution.

[0058] As a specific embodiment of the present invention, the process of adding the alkaline solution and the surfactant may be accompanied by stirring. The present invention has no special limitation on the stirring, as long as the mixture can be mixed evenly.

[0059] After obtaining the mixed solution, the present invention drips the tetraethoxysilane solution into the mixed solution. The present invention has no particular limitation on the dripping rate, as long as the solution can be added dropwise.

[0060] As a specific embodiment of the present invention, the mass ratio of the surface hydroxylated hexagonal boron nitride to the volume ratio of the solvent can be 1g:10-50mL, and can be specifically 1g:10mL, 1g:15mL, 1g:20mL, 1g:25mL, 1g:30mL, 1g:35mL, 1g:40mL, 1g:45mL or 1g:50mL; the volume ratio of the tetraethoxysilane to the solvent can be 1:4-30, and can also be 1:5-20; the mass ratio of the surfactant to the solvent can be 1:20-100, and can also be 1:30-80, and can further be 1:40-60; the mass ratio of the alkaline solution to the volume ratio of the solvent can be 1g:20-35mL, and can also be 1g:25-30mL.

[0061] As a specific embodiment of the present invention, the temperature of the hydrolysis reaction can be 15 to 35°C, specifically 15°C, 20°C, 25°C, 30°C or 35°C; the time of the hydrolysis reaction can be 12 to 36 hours, 18 to 30 hours, and further 20 to 26 hours. As a specific embodiment of the present invention, the hydrolysis reaction can be accompanied by stirring, and the present invention has no special limitation on the stirring, as long as it can fully react. In the present invention, after the hydrolysis reaction, the hydroxyl groups on the surface of the hexagonal boron nitride and the silicon dioxide form silicon-oxygen bonds through hydrolysis condensation, and the silicon dioxide is loaded onto the surface of the boron nitride through chemical bonding.

[0062] The invention grafts silicon dioxide after treating hexagonal boron nitride with a strong alkali, which not only improves the synergistic lubrication effect between the two, but also introduces hydroxyl active groups on the surface, which can increase the hydrophilicity of the silicon dioxide-loaded hexagonal boron nitride hybrid material, achieve the uniformity of its dispersion in the phenolic resin, and can also combine with the phenolic resin and textile fiber cloth in the form of hydrogen bonds, chemical bonds, etc. during the curing process, thereby increasing the bonding force between the filler (modified hexagonal boron nitride) and the phenolic resin and the textile fiber cloth, and significantly improving the mechanical strength of the phenolic laminated composite material and the wear resistance under water lubrication conditions.

[0063] As a specific embodiment of the present invention, the hydrolysis reaction may further include: separating the solid and liquid of the system after the hydrolysis reaction, washing and drying the solid obtained by the solid-liquid separation in sequence to obtain modified hexagonal boron nitride. As a specific embodiment of the present invention, the solid-liquid separation may be filtration; the washing detergent includes sequential water washing and ethanol solution washing, the water for the water washing may be deionized water, and the mass concentration of the ethanol solution for the ethanol solution washing may be 95-100%; the drying temperature may be 70-90°C, and may also be 75-80°C. The present invention has no special requirements for the drying time, as long as the solvent on the solid surface can be removed.

[0064] The present invention also provides the use of the modified hexagonal boron nitride described in the above technical solution or the modified hexagonal boron nitride prepared by the preparation method described in the above technical solution as a lubricant.

[0065] The present invention also provides a self-lubricating phenolic laminate composite material, comprising the following components in percentage by mass:

[0066] Phenolic resin 40-55%;

[0067] Textile fiber cloth 35-57%;

[0068] Lubricant 3-15%;

[0069] The lubricant is the modified hexagonal boron nitride described in the above technical solution or the modified hexagonal boron nitride prepared by the preparation method described in the above technical solution.

[0070] Calculated by mass percentage, the self-lubricating phenolic laminate composite material provided by the present invention comprises 40-55% phenolic resin, and may be 45-50%.

[0071] The self-lubricating phenolic laminate composite material provided by the present invention comprises 35-57% of textile fiber cloth, which may be 40-50%, or 45-48% by weight. As a specific embodiment of the present invention, the fibers in the textile fiber cloth may include one or more of polyester fiber, cotton fiber, acrylic fiber, polytetrafluoroethylene fiber, and aramid fiber, which may be specifically polyester fiber, cotton fiber, acrylic fiber, polytetrafluoroethylene fiber, or aramid fiber.

[0072] Calculated by mass percentage, the self-lubricating phenolic laminate composite material provided by the present invention includes 3-15% lubricant, can be 5-13%, and can also be 8-11%.

[0073] The self-lubricating phenolic laminate composite material provided by the present invention can have a compressive strength of 295-310 MPa, a compression modulus of 4.8-5 GPa, a friction coefficient of 0.15-0.22 under water lubrication conditions, and a volume wear rate of (1.8-2.2)×10 -6 mm 3 / Nm.

[0074] The self-lubricating phenolic laminate composite material provided by the present invention has the characteristics of fast friction running-in and high wear resistance under water lubrication conditions, wherein the hydrated boric acid layer formed by the in-situ hydrolysis of hexagonal boron nitride and the excellent self-lubricating performance of boron nitride, together with the textile fiber cloth, promotes the formation of a friction lubricating film at the friction interface, and the in-situ compounding of the loaded hard silicon dioxide enhances the load-bearing capacity of the friction lubricating film.

[0075] The present invention also provides a method for preparing the self-lubricating phenolic laminate composite material described in the above technical solution, comprising the following steps:

[0076] Mixing the lubricant, phenolic resin and diluent to obtain a phenolic resin mixed solution;

[0077] impregnating the textile fiber cloth with the phenolic resin mixed solution and then drying to obtain a pre-impregnated textile fiber cloth;

[0078] The pre-impregnated textile fiber cloth is formed and then sintered and cured to obtain the self-lubricating phenolic laminate composite material.

[0079] The present invention mixes the lubricant, phenolic resin and diluent to obtain a phenolic resin mixed solution. As a specific embodiment of the present invention, the mixing may include the following steps:

[0080] Mixing phenolic resin and part of diluent to obtain phenolic resin solution;

[0081] The phenolic resin solution and lubricant are mixed and then the remaining diluent is added.

[0082] As a specific embodiment of the present invention, the diluent may include ethanol or methanol; the solid content of the phenolic resin solution may be 60-80%, or 70-75%. As a specific embodiment of the present invention, the phenolic resin solution and the lubricant may be mixed by three-roll grinding.

[0083] After obtaining the phenolic resin mixed solution, the present invention impregnates the textile fiber cloth with the phenolic resin mixed solution and then dries to obtain a pre-impregnated textile fiber cloth. As a specific embodiment of the present invention, the amount of glue applied after the textile fiber cloth is impregnated with the phenolic resin mixed solution can be 45-65%, and can be specifically 45%, 50%, 55%, 60% or 65%. As a specific embodiment of the present invention, the drying temperature can be 100-120°C, and can also be 110-115°C; the drying time can be 1-10 minutes, and can also be 2-8 minutes. 。

[0084] After obtaining the pre-impregnated textile fiber cloth, the present invention forms the pre-impregnated textile fiber cloth and then sintering and curing it to obtain the self-lubricating phenolic laminate composite material. As a specific embodiment of the present invention, the forming can be winding; the winding temperature can be 110-130°C, specifically 110°C, 115°C, 120°C, 125°C or 130°C; the winding pressure can be 140-160N, specifically 140N, 145N, 150N, 155N or 160N; the winding tension can be 140-160N, specifically 140N, 145N, 150N, 155N or 160N. As a specific embodiment of the present invention, the sintering and curing includes sequentially performing the first sintering and curing, the second sintering and curing, and the third sintering and curing; the temperature of the first sintering and curing can be 75-85°C, specifically 75°C, 80°C or 85°C; the insulation time of the first sintering and curing can be 90-120min, specifically 90min, 95min, 100min, 105min, 110min, 115min or 120min. The present invention can heat up from room temperature to the temperature required for the first sintering and curing in 20min, and the room temperature can be 20-35°C, and can also be 25-30°C.

[0085] As a specific embodiment of the present invention, the temperature of the second sintering and curing can be 100-120°C, specifically 100°C, 105°C, 110°C, 115°C or 120°C; the insulation time of the second sintering and curing can be 90-120min, specifically 90min, 95min, 100min, 105min, 110min, 115min or 120min. The present invention can raise the temperature from the temperature of the first sintering and curing to the temperature required for the second sintering and curing in 10min.

[0086] As a specific embodiment of the present invention, the temperature of the third sintering and curing can be 140-160°C, specifically 140°C, 145°C, 150°C, 155°C or 160°C; the insulation time of the third sintering and curing can be 120-240min, specifically 120min, 150min, 180min, 200min, 220min, 230min or 240min. The present invention can raise the temperature from the temperature of the second sintering and curing to the temperature required for the third sintering and curing in 10min.

[0087] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0088] Example 1

[0089] The preparation method of modified hexagonal boron nitride is as follows:

[0090] 30 g of hexagonal boron nitride with an average particle size of 5 μm and 300 mL of a sodium hydroxide solution with a molar concentration of 5 mol / L were mixed under ultrasonic conditions for 20 min; surface activated hydrolysis (with stirring) was performed at 110° C. for 15 h and then filtered; the filtered solid was washed with deionized water until neutral and then dried at 80° C. to obtain hydroxylated hexagonal boron nitride;

[0091] Tetraethoxysilane and solvent (the solvent is a mixture of ethanol and water in a volume ratio of 1:5) are mixed in a volume ratio of 1:10 to obtain a tetraethoxysilane ethanol solution; 10 g of hydroxylated hexagonal boron nitride is dispersed in 200 mL of solvent, and ultrasonicated at room temperature for 15 minutes to obtain a hydroxylated hexagonal boron nitride dispersion; 6 g of ammonia alkaline solution and 2.4 g of decanyltrimethylammonium chloride (surfactant) are added to the hydroxylated hexagonal boron nitride dispersion in sequence to adjust the pH value of the system to 9, and after stirring and dispersing evenly, 30 mL of tetraethoxysilane ethanol solution is added dropwise, and then a hydrolysis reaction is carried out at 30° C. for 18 hours (with stirring); after the reaction is completed, the mixture is filtered, and the filtered solid is washed with deionized water and an ethanol solution with a mass concentration of 95% until it is neutral, and then dried at 80° C. to obtain modified hexagonal boron nitride.

[0092] The preparation method of the self-lubricating phenolic laminate composite material is as follows:

[0093] Phenolic resin and ethanol were mixed to obtain a phenolic resin ethanol solution with a solid content of 70%; 300 g of modified hexagonal boron nitride was added to 4285 g of the phenolic resin ethanol solution, the mixture was evenly dispersed by three-roll grinding, and then 2315 g of ethanol was added and stirred at a speed of 1000 rpm to obtain a phenolic resin mixed solution;

[0094] The 100 yarn count textile fiber cloth (woven from polyester fiber and cotton fiber) with desizing on the surface was impregnated in a phenolic resin mixed solution by continuous fiber impregnation, and dried continuously at 110° C. for 8 minutes to obtain a pre-impregnated textile fiber cloth, wherein the glue amount of the pre-impregnated textile fiber cloth was 55%;

[0095] The pre-impregnated textile fiber cloth is continuously wound and rolled into a tube material through a winding machine, and the winding process parameters are: winding temperature is 120°C, winding pressure is 150N, and winding tension is 150N; after the winding and rolling is completed, the product is placed in a high-temperature sintering furnace for high-temperature sintering and curing, and the sintering process is: linearly heating from 20°C to 80°C through 20min, and keeping warm at 80°C for 120min; linearly heating from 80°C to 100°C through 10min, and keeping warm at 100°C for 120min; linearly heating from 100°C to 160°C through 10min, and keeping warm at 160°C for 120min, and then naturally cooling to obtain a self-lubricating phenolic laminated composite material.

[0096] Example 2

[0097] Modified hexagonal boron nitride was prepared according to the method of Example 1;

[0098] The preparation method of the self-lubricating phenolic laminate composite material is as follows:

[0099] Phenolic resin and ethanol were mixed to obtain a phenolic resin ethanol solution with a solid content of 70%; 200 g of modified hexagonal boron nitride was added to 4285 g of the phenolic resin ethanol solution, and then 2315 g of ethanol was added and stirred at a speed of 1000 rpm to obtain a phenolic resin mixed solution;

[0100] The 100 yarn count textile fiber cloth (woven from polyester fiber and cotton fiber) with desizing on the surface is impregnated in a phenolic resin mixed solution by continuous fiber impregnation, and then dried at 110° C. for 5 minutes to obtain a pre-impregnated textile fiber cloth, wherein the glue amount of the pre-impregnated textile fiber cloth is 50%;

[0101] The pre-impregnated textile fiber cloth is continuously wound and rolled into a tube material through a winding machine, and the winding process parameters are: winding temperature is 120°C, winding pressure is 150N, and winding tension is 150N; after the winding and rolling is completed, the product is placed in a high-temperature sintering furnace for high-temperature sintering and curing, and the sintering process is: linearly heating from 20°C to 80°C through 20min, and keeping warm at 80°C for 120min; linearly heating from 80°C to 100°C through 10min, and keeping warm at 100°C for 120min; linearly heating from 100°C to 160°C through 10min, and keeping warm at 160°C for 120min, and then naturally cooling to obtain a self-lubricating phenolic laminated composite material.

[0102] Example 3

[0103] The preparation method of modified hexagonal boron nitride is as follows:

[0104] 30 g of hexagonal boron nitride with an average particle size of 8 μm and 300 mL of a sodium hydroxide solution with a molar concentration of 3 mol / L were mixed under ultrasonic conditions for 25 min; surface activated hydrolysis (with stirring) was performed at 120° C. for 30 h and then filtered; the filtered solid was washed with deionized water until neutral and then dried at 80° C. to obtain hydroxylated hexagonal boron nitride;

[0105] Tetraethoxysilane and a solvent (the solvent is a mixture of ethanol and water in a volume ratio of 1:5) are mixed in a volume ratio of 1:10 to obtain a tetraethoxysilane ethanol solution; 10 g of hydroxylated hexagonal boron nitride is dispersed in 200 mL of the solvent, and ultrasonicated for 15 min at room temperature to obtain a hydroxylated hexagonal boron nitride dispersion; 6 g of an alkaline ammonia solution and 2.4 g of decanyltrimethylammonium chloride (surfactant) are sequentially added to the hydroxylated hexagonal boron nitride dispersion to adjust the pH value of the system to 10, and after stirring and dispersing evenly, 45 mL of the tetraethoxysilane ethanol solution is added dropwise, and the mixture is stirred at 18°C ​​for 36 hours for hydrolysis reaction (with stirring); after the reaction is completed, the mixture is filtered, and the filtered solid is washed with deionized water and an ethanol solution with a mass concentration of ...% until it is neutral, and then dried at 80°C to obtain a modified hexagonal boron nitride.

[0106] A self-lubricating phenolic laminate composite material was prepared according to the method of Example 1.

[0107] Comparative Example 1

[0108] The preparation method of the traditional self-lubricating phenolic laminated composite material is as follows:

[0109] Take 200g of molybdenum disulfide, add it to 4285g of phenolic resin ethanol solution with a solid content of 70%, grind it by three rollers to obtain a modified phenolic resin glue solution in which molybdenum disulfide is uniformly dispersed, add 2315g of ethanol solution and stir at 1000rpm to obtain a modified phenolic resin diluted glue solution;

[0110] The conventional cotton fiber cloth with a yarn count of 100 and desized on the surface is impregnated in the modified phenolic resin diluted glue solution by continuous fiber impregnation, and then continuously dried at 100° C. to obtain a pre-impregnated cotton fiber cloth, wherein the glue amount of the pre-impregnated cotton fiber cloth is 50%;

[0111] The modified phenolic resin pre-impregnated cotton fiber cloth is continuously wound into a tube material through a winding machine, and the winding process parameters are: winding temperature is 120°C, winding pressure is 100N, and winding tension is 150N; after the winding and rolling is completed, the cotton fiber cloth phenolic laminated tube material is placed in a high-temperature sintering furnace for high-temperature sintering and curing, and the sintering process is: keeping warm at 80°C for 120min; keeping warm at 100°C for 120min; keeping warm at 120°C for 120min; keeping warm at 160°C for 120min, and then naturally cooling to obtain molybdenum disulfide modified cotton fiber cloth phenolic laminated material.

[0112] Comparative Example 2

[0113] It is a traditional phenolic laminated composite material, namely phenolic bakelite material, and the preparation method is as follows:

[0114] Take 4285g of phenolic resin ethanol solution with a solid content of 70%, add 1715g of ethanol solution, and obtain a phenolic resin diluted glue solution by high-speed stirring;

[0115] The conventional cotton fiber cloth with a yarn count of 100 and desized on the surface is impregnated in the diluted phenolic resin glue solution by continuous fiber impregnation, and then continuously dried at 100° C. to obtain a pre-impregnated cotton fiber cloth, wherein the glue amount of the pre-impregnated cotton fiber cloth is 50%;

[0116] The modified phenolic resin pre-impregnated cotton fiber cloth is continuously wound into a tube material through a winding machine, and the winding process parameters are: winding temperature is 110°C, winding pressure is 100N, and winding tension is 150N; after the winding and rolling is completed, the cotton fiber cloth phenolic laminated tube material is placed in a high-temperature sintering furnace for high-temperature sintering and curing, and the sintering process is: keeping warm at 80°C for 120min; keeping warm at 100°C for 120min; keeping warm at 120°C for 120min; keeping warm at 160°C for 120min, and then naturally cooling to obtain the cotton fiber cloth phenolic laminated material, that is, phenolic bakelite material.

[0117] The modified hexagonal boron nitride prepared in Example 1 was examined by scanning electron microscopy to obtain SEM and EDX element analysis diagrams, as shown in FIG. Figure 1 As shown. Figure 1 It can be seen that the surface of the modified hexagonal boron nitride is uniformly covered with nanoparticles with a particle size of 10 to 30 nm. From the EDX elemental analysis diagram, it can be seen that the surface of the modified hexagonal boron nitride is uniformly covered with a large amount of silicon and oxygen elements, indicating that the surface of the modified hexagonal boron nitride successfully synthesizes silicon dioxide nanoparticles with a particle size of 10 to 30 nm bonded by silicon oxygen bonds; the surface roughness and surface area of ​​the modified hexagonal boron nitride are significantly increased. This will significantly enhance the contact area and mechanical interlocking effect of the interface between the modified hexagonal boron nitride and the phenolic resin, and will greatly increase the interfacial bonding force between the modified hexagonal boron nitride and the phenolic resin.

[0118] The silica loading amount is obtained by weighing the mass of the modified hexagonal boron nitride after modification minus the mass of the unmodified boron nitride, and then dividing the mass by the mass of the unmodified boron nitride. By calculation, it is found that the silica loading amounts in the modified hexagonal boron nitride prepared in Examples 1 to 3 are 23.1 wt%, 23.1 wt% and 18.4 wt%, respectively.

[0119] The mechanical properties and water lubricity of the phenolic laminates prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were tested respectively. The testing steps are as follows:

[0120] (1) The compression strength test is carried out in accordance with the Test Method for Compression Properties of Fiber Reinforced Plastics (GB / T1448-2005). The corresponding standard test specimens are processed and the compression strength is measured using a universal testing machine.

[0121] (2) The friction and wear performance test was carried out in accordance with the "Plastic Sliding Friction and Wear Test Method" (GB / T3960-2016). The test equipment was the MRH-1A ring-block type friction and wear tester. The friction tests were all carried out at room temperature. In the water lubrication test, the sample and the counterpart were completely immersed in deionized water. The test conditions were: the counterpart steel ring was QSn7-0.2, Ra was 0.1-0.2μm, the diameter of the counterpart ring was 50mm, the test load was 132N, the sliding speed was 0.36m / s, and the test time was 2h. During the test, the friction coefficient was directly read out by the equipment, the wear width was measured using a three-dimensional surface profiler, and the volume wear rate was calculated. The friction and wear performance tests of the samples in the embodiment and the comparative example were repeated at least three times, and the average value was taken; the test results are listed in Table 1.

[0122] Table 1 Performance of phenolic laminates in Examples 1 to 3 and Comparative Examples 1 to 2

[0123]

[0124] It can be seen from Table 1 that, compared with the phenolic laminated composite material prepared in the comparative example, the self-lubricating phenolic laminated composite material prepared with modified hexagonal boron nitride as the lubricating phase provided by the present invention has higher compression resistance and exhibits very excellent friction and wear performance under water lubrication conditions. The friction coefficient of the self-lubricating phenolic laminated composite material prepared in Example 1 under water lubrication conditions is reduced by 36% compared with that of Comparative Example 2, and the wear resistance is improved by about 300%.

[0125] The self-lubricating phenolic laminated composite material prepared by using modified hexagonal boron nitride as the lubricating phase can further improve the compression resistance of the phenolic laminated composite material, so that the phenolic laminated composite material has both low friction and high wear resistance, and has excellent water-lubricated tribological performance.

[0126] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A modified hexagonal boron nitride, characterized in that: The invention comprises hexagonal boron nitride and silicon dioxide bonded to the hexagonal boron nitride by silicon-oxygen bonds.

2. The modified hexagonal boron nitride according to claim 1, characterized in that: The mass ratio of silicon dioxide to hexagonal boron nitride in the modified hexagonal boron nitride is 5 to 30:

100.

3. The method for preparing modified hexagonal boron nitride according to claim 1 or 2, characterized in that: The following steps are involved: The hexagonal boron nitride and the strong base solution are first mixed to perform surface hydrolysis activation to obtain hydroxylated hexagonal boron nitride; The hydroxylated hexagonal boron nitride, tetraethoxysilane, surfactant, alkaline solution and solvent are mixed for a second time and subjected to a hydrolysis reaction to obtain the modified hexagonal boron nitride.

4. The preparation method according to claim 3, characterized in that: The strong alkali solution includes one or more of a sodium hydroxide solution, a potassium hydroxide solution and a lithium hydroxide solution; the molar concentration of the strong alkali solution is 3 to 6 mol / L; The particle size of the hexagonal boron nitride is 5 to 10 μm; the mass of the hexagonal boron nitride and the volume ratio of the strong alkaline solution are 1 g: 10 to 30 mL; The temperature of the surface hydrolysis activation is 90 to 120° C.; the time of the surface hydrolysis activation is 10 to 36 hours.

5. The preparation method according to claim 3, characterized in that: The alkaline solution includes one or more of a mixed solution of NH3 and NH4Cl, a mixed solution of NH3 and NH4HCO3, and NH3·H2O; the pH value of the alkaline solution is 8 to 10; The surfactant includes one or more of dodecyltrimethylammonium chloride, N-dodecyldimethylamine, fatty acid soap, sodium cis-9-octadecenoate and sodium laurate soap; The solvent includes an organic solvent and water, wherein the organic solvent includes one or more of ethanol, ethylene glycol, glycerol, tetrahydrofuran, toluene, chlorobenzene and dichlorobenzene; the volume ratio of the organic solvent to water is 1:4-6; The mass ratio of the surface hydroxylated hexagonal boron nitride to the volume ratio of the solvent is 1 g: 10-50 mL; The volume ratio of tetraethoxysilane to solvent is 1:4-30; The mass ratio of the surfactant to the solvent is 1:20 to 100; The mass ratio of the alkaline solution to the volume of the solvent is 1 g: 20-35 mL; The temperature of the hydrolysis reaction is 15-35° C. and the time is 12-36 hours.

6. Use of the modified hexagonal boron nitride according to claim 1 or 2 or the modified hexagonal boron nitride prepared by the preparation method according to any one of claims 3 to 5 as a lubricant.

7. A self-lubricating phenolic laminate composite material, characterized in that: Includes the following components in percentage by mass: Phenolic resin 40-55%; Textile fiber cloth 35-57%; Lubricant 3-15%; The lubricant is the modified hexagonal boron nitride according to claim 1 or 2 or the modified hexagonal boron nitride prepared by the preparation method according to any one of claims 3 to 5.

8. The self-lubricating phenolic laminate composite material according to claim 7, characterized in that: The fibers in the textile fiber cloth include one or more of polyester fibers, cotton fibers, acrylic fibers, polytetrafluoroethylene fibers and aramid fibers.

9. The method for preparing the self-lubricating phenolic laminate composite material according to claim 7 or 8, characterized in that: The following steps are involved: The lubricant, phenolic resin and diluent are mixed to obtain a phenolic resin mixed solution; impregnating the textile fiber cloth with the phenolic resin mixed solution and then drying to obtain a pre-impregnated textile fiber cloth; The pre-impregnated textile fiber cloth is formed and then sintered and cured to obtain the self-lubricating phenolic laminate composite material.

10. The preparation method according to claim 9, characterized in that: The amount of glue applied after the textile fiber cloth is impregnated with the phenolic resin mixed solution is 45 to 65%; The drying temperature is 100-120°C and the drying time is 1-10 minutes; The sintering and curing comprises sequentially performing a first sintering and curing, a second sintering and curing, and a third sintering and curing; The temperature of the first sintering and curing is 75-85° C., and the holding time of the first sintering and curing is 90-120 min; The temperature of the second sintering and curing is 100-120° C., and the insulation time of the second sintering and curing is 90-120 min; The temperature of the third sintering and curing is 140-160° C., and the heat preservation time of the third sintering and curing is 120-240 minutes.

Citation Information

Patent Citations

  • Preparation method of self-lubricating ceramic cutting tool material comprising spherical nanometer silicon dioxide coated hexagonal boron nitride composite powder

    CN104844178A

  • SiC-coated hexagonal boron nitride composite powder modified self-lubricating ceramic cutter material and preparation method thereof

    CN104844225A

  • Preparation method of spherical nano silica-coated hexagonal boron nitride composite powder

    CN104974817A

  • Layered composite material and preparation method thereof, and self-lubricating fiber fabric composite material and preparation method and application thereof

    CN114645451A

  • Silicon carbide whisker modified boron nitride composite material, preparation method and application thereof, boron nitride complex and preparation method thereof

    CN114804904A